Impact of mothers’ knowledge and support for sustaining exclusive breastfeeding - Surender, K; Kumar, K Naresh; Nikhitha, V; Bhargavi, S Devi Priya; Kumar, G Raj (Indian Journal of Child Health, 2019)
Background: Breast milk is the best milk for the baby. It is beneficial for the baby as well as the mother, family, and nation. In spite of an established fact, still, a very low percentage (44.2%) is implementing it. Objective: The objective of this study was to find out the knowledge, concerns, and difficulties in breastfeeding and the obstacles in the practicing breastfeeding. Materials and Methods: A cross-sectional study was done at pediatric clinics in Warangal. A total of 1010 lactating mothers who were presenting for regular check-ups were enrolled. After taking oral consent, mothers were interviewed through a predesigned questionnaire containing 50 questions on pre- and post-natal counseling received, and knowledge of exclusive breastfeeding, importance of skin-to-skin contact (SSC), and their educational status and hygiene. The entire session of interview was carried out in the optimum privacy to create a favorable environment of acquiring the data. Results: Of 1010 mothers enrolled, only 25.4% had received antenatal counseling, 15.8% had received postnatal counseling regarding exclusive breastfeeding, 56.4% followed exclusive breastfeeding (EBF), and SSC was maintained by only 2%, after delivery which played an important role in breastfeeding, p=0.000003 for antenatal counseling and EBF. Conclusion: More attention should be given in educating mothers when they conceive, regarding breastfeeding, its problems and skills, during their first visit to health-care professionals.